Aplikasi Limbah Padat Karet Remah Pada Tanah Podsolik Merah Kuning Terhadap Ketersediaan Hara Makro Dan Perbaikan Sifat Fisika Tanah - Muhammad Helmy Abdillah; Muhammad Aldi (Universitas Lambung Mangkurat, 2020)
The chemical properties of Podsolic Red-Yellow soil have pH is very acidic to slightly acidic, low to moderate percentage of C-organic, low to moderate P, and low status of K, Ca, Mg, Na, and other saturation of bases. Also, the physical characteristics of the Red-Yellow Podsolic soil show a distinctive characteristic, as bulk density soil index of 1.30 - 1.50 g.cm-3, with low water absorption. The chemical and physical properties are bad enough to make Red-Yellow Podsolic soil have a low ability to provide macronutrients needed by plants. Organic matter is proven to be able to control nutrient availability in mineral soils. The potentials for organic material that has been completely decomposed is crumb rubber solid waste. The use of crumb rubber solid waste material as organic material is expected to be able to influence the availability of macronutrients and improve the physical characteristics of the Podsolic Red-Yellow soil. This study aims to find differences in the availability of NH4+ NO3-, H2PO4-, K-exchangeable, C-organic and to compare the treatments that produce the best index of soil bulk density, increase the percentage of water content, and determine the soil temperature of Red-Yellow Podsolic with the application of crumb rubber solid waste with difference level, statistical test with through the index of mean difference Tukey’s test on level α 5%. In this research it was concluded that the application of crumb rubber solid waste could increase soil pH, provide levels of NH4+, NO3-, H2PO4, K-exchangeable, C-organic and reduce soil bulk density index, increase water content and soil temperature compared to not using crumb rubber solid waste. PCr3 treatment showed the highest yield at pH, NH4+, H2PO4, C-organic and increased water content, but it was not significantly different than PCr2 treatment, whereas PCr2 was significantly different from PCr3 in providing NO3-, K-exchangeable.